Preparing future accountants: integrating Artificial Intelligence (Al) competencies into the accounting curriculum - Mohd Noor, Marjan; Shanmugam, Jaya Kumar; Muslimin, Mohamad Siri; Haidzir, Muhammad Hafidz (Faculty of Accountancy, 2025)
The fast pace of Artificial Intelligence (AI) technologies' development is transforming the professional accounting landscape. While automation, data analysis, and machine learning capacities become the norms of business, the accounting professional needs to acquire skills in accordance with the technological advancement. Classical training for accountants as a starting point now cannot suffice to address the requirements of the digital economy. Therefore, it is a requirement to include AI-related abilities in accounting programs to keep future accountants updated and competitive. This article maintains that AI skills are an integral component of accounting training, identifies the essential AI-related skills to be integrated, and offers guidelines for integrating these skills successfully into accounting courses.